Phytochemicals in leaves of Cotoneaster mongolica, their antioxidative, and acetylcholinesterase inhibitory activity - Gendaram, Odontuya (Mongolian Journal of Chemistry, 2019)
The phytochemicals in the leaves of Cotoneaster mongolica Pojark, as well as their antioxidant and acetylcholinesterase (AChE) inhibitory activity were studied. The methanol extract of the leaves showed acetylcholinesterase inhibitory activity (IC50, 32.61 ± 0.51 μg/mL). The n-butanol fraction of this extract exhibited DPPH radical scavenging (IC50, 55.70 ± 0.15 μg/mL) and AChE inhibitory activity (IC50, 72.50 ± 0.60 μg/mL). From the n-butanol fraction quercetin (1), hyperoside (2), kaempferol-5-O-β-D-glucopyranoside (3), sissotrin (4), ursolic acid (5), corosolic acid (6), euscaphic acid (7), prunasin (8), (2R)-mandeloyl-β-D-glucopyranose (9), (Z)-3-hexenyl-O-α-L-rhamnopyranosyl-(1→6)-β-D-glucopyranoside (10), benzyl- O-α-L-rhamnopyranosyl-(1→6)-β-D-glucopyranoside (11) and arbutin (12) have been isolated and identified. Hyperoside, one of the major constituents among the isolated compounds, was active in both tested assays. Flavonol derivatives could provide the activity of this plant species.